2020
DOI: 10.37506/ijfmt.v14i4.12045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Parkia speciosa Hassk Peels Extract on Total Cholesterol Levels of Hypercholesterolemia Rats

Abstract: Background: This research aimed to examine the secondary metabolites in the ethanol extract of Parkia speciosa Hassk peels and determine the effect of the P. speciosa Hassk peels on the reduction in total cholesterol levels of male hypercholesterolemia white rats.Methods: Thirty white male rats were divided into six treatment groups (n=5): Group I: normal control (0.5% CMC Na suspension), Group II: negative control (high cholesterol feed), Group III: positive control (suspension simvastatin), Group IV, V, VI: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A study by Tandi et al (2020) showed the effects of ethanol extract of P. speciosa peels on total cholesterol levels in the hypercholesterolemia rat model [ 71 ]. In that study, oral administration at the dose of 300 mg/kg daily reduced 52.73% of total cholesterol levels in hypercholesterolemia mice compared to the negative control group after 35 days.…”
Section: Pharmacological Potential Of P Speciosa E...mentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Tandi et al (2020) showed the effects of ethanol extract of P. speciosa peels on total cholesterol levels in the hypercholesterolemia rat model [ 71 ]. In that study, oral administration at the dose of 300 mg/kg daily reduced 52.73% of total cholesterol levels in hypercholesterolemia mice compared to the negative control group after 35 days.…”
Section: Pharmacological Potential Of P Speciosa E...mentioning
confidence: 99%
“…In that study, oral administration at the dose of 300 mg/kg daily reduced 52.73% of total cholesterol levels in hypercholesterolemia mice compared to the negative control group after 35 days. The effect of P. speciosa extract was comparable with the effect of simvastatin, which reduced total cholesterol levels by 57.27% [ 71 ].…”
Section: Pharmacological Potential Of P Speciosa E...mentioning
confidence: 99%
“…Half of this figure is in Asia such as India, China, and Indonesia. Indonesia is the 6th country with the most diabetes sufferers in the world (Tandi et al, 2020a).…”
Section: Introductionmentioning
confidence: 99%